2018
DOI: 10.1038/s41598-018-33616-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral facilitation and increased brain responses from a high interference working memory context

Abstract: Many real-life situations require flexible behavior in changing environments. Evidence suggests that anticipation of conflict or task difficulty results in behavioral and neural allocation of task-relevant resources. Here we used a high- and low-interference version of an item-recognition task to examine the neurobehavioral underpinnings of context-sensitive adjustment in working memory (WM). We hypothesized that task environments that included high-interference trials would require participants to allocate ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
(70 reference statements)
3
3
0
Order By: Relevance
“…This pattern may be the result of strategic choices of the participants, in which they increased effort with more countdowns, while at the same time focusing on a subset of component tasks. Such behavioral facilitation from increasing task demands were recently demonstrated within the context of working memory and executive control (Samrani, Marklund, Engström, Broman, & Persson, 2018). Moreover, and partly in line with previous studies (Kubik et al, 2018(Kubik et al, , 2019Todorov et al, 2014;Mäntylä, 2013), performance on this best countdown was predicted by participants' spatial (mental rotation) abilities, even after controlling for working memory (binding) skills.…”
Section: Discussionsupporting
confidence: 84%
“…This pattern may be the result of strategic choices of the participants, in which they increased effort with more countdowns, while at the same time focusing on a subset of component tasks. Such behavioral facilitation from increasing task demands were recently demonstrated within the context of working memory and executive control (Samrani, Marklund, Engström, Broman, & Persson, 2018). Moreover, and partly in line with previous studies (Kubik et al, 2018(Kubik et al, , 2019Todorov et al, 2014;Mäntylä, 2013), performance on this best countdown was predicted by participants' spatial (mental rotation) abilities, even after controlling for working memory (binding) skills.…”
Section: Discussionsupporting
confidence: 84%
“…Results from preceding stimuli were observed in the lower part of Figure 1, where the EEG dependence was found in the correlation of the properties of the current and the immediately prior stimuli. Moreover, prior research has found no evidence of any deficiency in N100 type potentials (Mugruza-Vassallo, 2016b;Mugruza-Vassallo and Potter, 2019) in agreement with Rosburg (2018). Likewise, the research of Samrani et al (2018) also involved the context of working memory relating to stimuli.…”
Section: Introductionsupporting
confidence: 67%
“…Moreover, Mugruza-Vassallo's experiments have not found evidence of any de ciency in N100 type potentials in agreement with Rosburg [18]. Likewise, Samrani and colleagues [19] have also involved the context of work memory related to stimuli. Considering the dependence of the previous answer as a possible Markov process, the present research has considered a subset of characteristics to simplify the videogame than the case of Torres-Tejada and colleagues [10], where 5 types of stimuli were used (see part upper of Figure 1).…”
Section: Introductionsupporting
confidence: 58%